Methicillin-resistant Staphylococcus aureus Clones, Western Australia - Coombs, Geoffrey W. (Centers for Disease Control and Prevention, 2006)
Community-associated methicillin-resistant Staphylococcus aureus (MRSA) was first reported in Western Australia in the early 1990s from indigenous peoples living in remote areas. Although a statewide policy of screening all hospital patients and staff who have lived outside the state for MRSA has prevented the establishment of multidrug-resistant epidemic MRSA, the policy has not prevented SCCmec type IV and type V MRSA clones from becoming established. Of the 4,099 MRSA isolates analyzed (referred to the Gram-positive Bacteria Typing and Research Unit) from July 2003 to December 2004, 77.5% were community-associated MRSA (CA-MRSA). Using multilocus sequence/staphylococcal chromosome cassette mec typing, 22 CA-MRSA clones were characterized. Of these isolates, 55.5% were resistant to >1 non–β-lactam antimicrobial drug. Five Panton-Valentine leukocidin (PVL)–positive CA-MRSA clones were identified. The emergence of multidrug-resistant CA-MRSA clones and the detection of PVL toxin genes in clones previously reported as PVL negative is a major public health concern.